2021
DOI: 10.1088/1757-899x/1092/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the MFlex monitoring system using Mahalanobis-Taguchi system

Abstract: Methadone Flexi Dispensing Service (MFlex) has been officially re-branded from Methadone 1Malaysia Service (M1M) since 2nd January 2019. Patients under MFlex are frequently taking their methadone according to a plan provided by pharmacist at public clinic. From the dose monitoring taken annually, pharmacists can predict critical patients based on high monthly dose increases. However, the current monitoring system is written documentation with total doses that cannot accurately measure addiction levels and slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Kamil et al [38] concluded that MTS and TDABC are great tools and feasible to be implemented in the electronic industry. Saad et al [39] developed an MTS-based graphical user interface to analyze and classify normal and abnormal patients under MFlex service for a better monitoring system. Ramlie et al [40] concluded that none of the four thresholding methods outperformed one over the others in (if it is not for all) most of the datasets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Kamil et al [38] concluded that MTS and TDABC are great tools and feasible to be implemented in the electronic industry. Saad et al [39] developed an MTS-based graphical user interface to analyze and classify normal and abnormal patients under MFlex service for a better monitoring system. Ramlie et al [40] concluded that none of the four thresholding methods outperformed one over the others in (if it is not for all) most of the datasets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[36] found that MTS and TDABC are a great resource that can be easily used in the electronic industry. [37] used the MFlex service to make the tracking system better by creating an MTS-based graphical user interface for analyzing and sorting patients into groups of normal and abnormal variants. According to [38], none of the four thresholding approaches outperformed the others in almost all of the datasets.…”
Section: Introductionmentioning
confidence: 99%